Defects of eucalypt wood associated with frost damage in Entre Ríos, Argentina - García, María de los Ángeles; Mastrandrea, Ciro Andrés (Instituto de Ecología, A.C., 2018)
We studied the association of visible frost damage with wood defects of Eucalyptus grandis trees affected by frost. Four months after frosts occurrence we classified 40 trees from a three-years-old stand in three classes of damage: no visible frost damage; frozen top; completely frozen crown; at the same time we measured trees height (H) and diameter at breast height (DBH) and after two years we measured 19 trees of the three classes of frost damage again and then we cut them. We also assessed the dynamic modulus of elasticity (DMoE) of the basal and the second logs and recorded the presence of pith, rot, cracks and kino on timber boards. Trees with no apparent frost damage showed significantly higher height and DBH compared with trees from the other classes, whereas by the second measurement trees with completely frozen crown presented significantly lower DBH than those from the other classes. DMoE of second logs was significantly higher in trees with no apparent frost damage compared with trees with completely frozen crown. We found rot only in timber boards from trees with frost damage, but we found no significant differences in the number of timber boards with rot between the two classes with visible frost damage. Association of cracks with frost damage was not significant. The classes of damage used in this study allowed to detect rot on tables and to differentiate trees according to DMoE of logs.